El legado historiográfico de Ibn Khaldūn en la discusión poscolonial: perspectiva desde Al-Ándalus - García Fernández, Javier (El Colegio de México, 2023)
This text aims to construct new, non-Eurocentric views of world history by recovering the legacy of Ibn Khaldūn (1332–1402) and incorporating it into postcolonial discussions. The article argues that non-European and non-Western references are necessary for a philosophy of history that recognizes the existence of plural experiences, epistemologies, and worldviews. The author develops ideas for a history of global thought from the Western Mediterranean experience.